Protein profiles, antimicrobial activity of Common Sunda Toad, Duttaphrynus melanostictus paratoid secretions and its ethical dimension on the consumption of amphibians for medical purposes - Muhamad Syafiq bin Ahmad Zahari (Kulliyyah of Science, International Islamic University Malaysia, 2017)
The emergence of multiple strains pathogens especially Multi-drug Resistant Organisms (MDROs) have led to an intensive and extensive exploration of natural products sources. Among the natural product sources are known from plants and animals. In this study, antimicrobial peptides from animal are known to possess such therapeutic effects against a wide range of pathogen. Antimicrobial peptides from Common Sunda Toad, Duttaphrynus melanostictus paratoid secretions were extracted using Norepinephrine Hydrochloride salts treatment before being concentrated for its partial purification of peptides through Ammonium Sulphate precipitation. The pooled partial purified peptides were tested for its protein profile through 12% SDS-PAGE and different weight of peptides were detected with 15 kDa being the lightest and 260 kDa being the heaviest. After partial purification, the peptides were tested for its antimicrobial properties against Staphylococcus aureus (ATCC 25923), Escherichia coli (ATCC 8739), Bacillus cereus (ATCC 11778), Salmonella typhimurium (IMR S 974/05 B), Staphylococcus epidermidis (ATCC 12228), Klebsiella pneumonia (ATCC 700603), clinically isolated Methicillin-resistant Staphylococcus aureus and fungal strain Candida albicans (IMRC 533/11A). The screening of its bioactivity was first performed using Kirby-Bauer Disc Diffusion technique. The secretions were proven to inhibit the growth of all pathogens except MRSA at different concentration ranging from 1000 µg/ml. 500 µg/ml and 250 µg/ml and it was achieved through Minimum Inhibitory Concentration (MIC), Minimum Bactericidal Concentration (MBC) and Minimum Fungicidal Concentration (MFC). The assay was further explained in mode of action in which it successfully proven in the lysis of nucleic acid and protein through 260 nm and 280 nm leakage. In addition to this, the aspect of utilizing amphibian as medicinal sources in terms of Islamic Jurisdiction have been decided.